Marketing risk analysis of red chili - Atahasi Ronokusumo; Ktut Silvanita Mangani (JURNAL MANAJEMEN, 2021)
This study aims to determine the marketing risks as a whole in red chili agribusiness in the Cibedug village, Ciawi area. West Java is one of the chili agribusiness centers closest to the capital city which is a very large market potential. Starting with a group discussion forum among red chili farmers, the authors use interviews as well as surveys of red chili agribusiness entrepreneurs. Data analysis was carried out in a simple qualitative and quantitative way that found at least 10 (ten) unwanted events and the impact of existing opportunities, unwanted events that must be prioritized to be mitigated. The most extreme risk of unwanted events namely different retail price constraints; end consumers who don't take much; profit margins are being eroded by unexpected costs and difficult to find marketing channels that buy routinely.